Mutations and homologous recombination induced in mammalian cells by metabolites of benzo[a]pyrene and 1-nitropyrene. - Maher, V M (1987)
Metabolites of two structurally related chemical carcinogens, benzo[a]pyrene and 1-nitropyrene, were compared for their ability to cause cytotoxicity and induce mutations in normally repairing or nucleotide excision repair-deficient diploid human fibroblasts; for their ability to induce mutations in a defined gene sequence, supF, when a plasmid containing adducts formed by these carcinogens replicates in human 293 cells; and for their ability to induce homologous recombination between duplicated genes in mouse L cells. Both of the metabolites tested, i.e., (+/-)-7 beta,8 alpha-dihydroxy-9 alpha,10 alpha, epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene (BPDE) and 1-nitrosopyrene (1-NOP), form adducts on guanine. BPDE binds principally at the N2 position of guanine; 1-NOP binds to guanine at the C8 position. Results of the studies in diploid human cells indicated that when compared on the basis of equal numbers of DNA adducts, BPDE is more effective than 1-NOP in inducing mutations in DNA repair-proficient cells, but when compared in repair-deficient xeroderma pigmentosum human cells that do not remove such adducts from their DNA, the frequency of mutants induced per adduct is equal. These results suggest that during the time available for repair of potentially mutagenic lesions, repair-proficient human cells excise 1-NOP adducts more rapidly than they excise BPDE adducts. Molecular analysis of the specific kinds of mutations induced when a plasmid containing BPDE residues was allowed to replicate in human cells showed that BPDE induces mainly base substitution mutations, predominantly G:C to T:A transversions.(ABSTRACT TRUNCATED AT 250 WORDS)